Introducing vigilant audiences - Gabdulhakov, Rashid; Huang, Qian; Trottier, Daniel; Open Book Publishers (Open Book Publishers, 2020)
"This ground-breaking collection of essays examines the scope and consequences of digital vigilantism - a phenomenon emerging on a global scale, which sees digital audiences using social platforms to shape social and political life. Longstanding forms of moral scrutiny and justice seeking are disseminated through our contemporary media landscape, and researchers are increasingly recognising the significance of societal impacts effected by digital media. The authors engage with a range of cross-disciplinary perspectives in order to explore the actions of a vigilant digital audience - denunciation, shaming, doxing - and to consider the role of the press and other public figures in supporting or contesting these activities. In turn, the volume illuminates several tensions underlying these justice seeking activities - from their capacity to reproduce categorical forms of discrimination, to the diverse motivations of the wider audiences who participate in vigilant denunciations. This timely volume presents thoughtful case studies drawn both from high-profile Anglo-American contexts, and from developments in regions that have received less coverage in English-language scholarship. It is distinctive in its focus on the contested boundary between policing and entertainment, and on the various contexts in which the desire to seek retribution converges with the desire to consume entertainment. Introducing Vigilant Audiences will be of great value to researchers and students of sociology, politics, criminology, critical security studies, and media and communication. It will be of further interest to those who wish to understand recent cases of citizen-led justice seeking in their global context."--Publisher's website.
Contents -- Acknowledgements -- Notes on Contributors -- Introducing Vigilant Audiences -- 'For the Greater Good?' -- Vigilantism in Online Pop Culture Fandoms -- Contesting the Vulgar Hanmai Performance from Kuaishou: Online Vigilantism toward Chinese -- Underclass Youths on Social Media Platforms -- 'I don't think that's very funny': Scrutiny of Comedy in the Digital Age -- Criticism of Moral Policing in Russia: Controversies around Lev Protiv in Moscow -- Far-Right Digital Vigilantism as Technical Mediation: Anti-Immigration Activism on YouTube -- Empowerment, Social Distrust or Co-production of Security: A Case Study of Digital Vigilantism in Morocco -- 'This Web Page Should Not Exist': A Case Study of Online Shaming in Slovenia -- 'Make them famous': Digital Vigilantism and Virtuous Denunciation after Charlottesville -- Doxing as Audience Vigilantism against Hate Speech -- Citizens as Aides or Adversaries? Police Responses to Digital Vigilantism -- More Eyes on Crime?: The Rhetoric of Mediated Mugshots -- Index.
Available through Open Book Publishers.
Includes bibliographical references.
Mode of access: World Wide Web.
Keywords: Democracy -- Citizen participation; Digital media -- Social aspects; Internet -- Social aspects; Mass media -- Technological innovations -- Social aspects; Political participation